Village Headman and Their Financial Role in Managing Credit Institutions during Colonial Times - Rinardi, M. Hum., Haryono; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri; Mufidah, Rafngi (Department of History, Faculty of Humanities, Diponegoro University, 2024)
This study examines the role of the village headman in overseeing village credit institutions (Village Banks) during the colonial era in Indonesia. Using a historical approach, it investigates the financial duties of the headman and the advantages he derived from these institutions. Village Banks, established by the colonial government, were community-based credit systems designed to meet specific economic needs in rural areas. The paper focuses on the headman’s administrative role within the Village Bank framework, analyzing his interactions with the institution and his significant influence over village finances. It argues that the involvement of local elites, particularly the headman, was crucial to the establishment, operation, and success of Village Banks. The patron-client relationships inherent in rural society also played a key role in facilitating the functioning of these credit institutions. However, this system had its drawbacks, as the headman and other elites often exploited it for personal gain, hindering the full development of Village Banks. In this context, effective bureaucratic oversight became essential to ensure the progress and proper functioning of the Village Banks.